STUDI WAKTU APLIKASI PUPUK KOMPOS LEGUMINOSA DENGAN BIOAKTIVATOR Trichoderma sp. TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI MERAH (Capsicum annuum L.) - Amin, Fazrul; Yoseva, Sri; ', Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Chili is really needed to complete consumption of family needs and industrial fabrics. One of the attempting to increase chili’s production is by repairing of cultivation technique with bioactivator Trichoderma sp. precisely. It has been researched about at the application time of leguminous compost by bioactivator Trichoderma sp. towards the growth and production of chili (Capsicum annuum L.) in incubator Gauze House of Agribusiness, Agriculture Faculty, University of Riau. This study was conducted from January to June 2014. The purpose of this study to invent the best application time of leguminous compost by bioactivator Trichoderma sp. towards the growth and production of chili and to determine all variables correlation. The research was implemented experimentally by Completely Randomized Design (CRD) consisting of 5 treatments as follows: application time of leguminous composts by bioactivator Trichoderma sp. two weeks before planting (W1), a week before planting (W2), on the planting time (W3), a week after planting (W4), two weeks after planting (W5). Every treatment consisted 3 replications, each experiment consisted 3 plants poly bags and they all be the sample. Observation parameters were stem diameter, dichotomous height, plant height, crown width, days to flowering, harvesting time, harvest quantity, fruit diameter, fruit length, weight per fruit and fruit weight per plant. The research result showed that the treatment of application time of compost differently has an influence towards the period of chili’s harvesting. The application of leguminous composts by bioactivator Trichoderma sp. two weeks before planting is the best treatment to speed the period of chili’s harvesting. Stem diameter, dichotomous height, plant height, days to flowering, harvesting time, harvest quantity, fruit diameter, fruit length positivly correlated with fruit weight per plant but crown width negativly correlated with weight per fruit. Keywords: Chili, Compost Aplication Time, Leguminosa, Trichoderma sp.